HUBUNGAN EFIKASI DIRI DAN DUKUNGAN SOSIAL TERHADAP KINERJA PRAKTEK MAHASISWA AKADEMI KEBIDANAN DI RUMAH SAKIT UMUM BOYOLALI - Budiadi, Budiadi (2011)
Background: General Hospital Pandan Arang well as hospitals to provide services (Public Hospital) is also an education where students from several universities (Theaching Hospital). But most of the students at the General Hospital have not implemented optimally obligations. Many of the factors that affect student performance practice, such as self efficacy and social support. Objective: To analyze the relationship between self efficacy and social support on the performance of college students practice midwifery in the General Hospital Boyolali. Methods: This study uses quantitative research design. Research conducted at the General Hospital Boyolali. The number of samples of 50 students who conducted the performance academy midwifery practice in the General Hospital Boyolali, using a random quota sampling technique. Independent variables were self-efficacy and social support, while the dependent variable of performance practice. Collecting data using questionnaires and secondary data that exist in the hospital. Data analysis using normality test, linearity and multiple linear regression analysis. Results: show that there is a very significant positive relationship between self efficacy and social support on performance practice, with a correlation coefficient (r) of 0, 696, p = 0.000 (p <0.05) (self efficacy), 0.775; p = 0.000 (p <0.05) (social support). Effective contribution of the variable self-efficacy and social support is 67.9% which is shown by the determinant coefficient (r2) of 0.679. Conclusion: there is a relationship between self efficacy and social support on the performance of college students practice midwifery either partial or jointly significantly.